Characteristics of Work-related Fatal Injuries Among Aged Workers in Republic of Korea - Jungsun Park; Jong-shik Park; Younghoon Jung; Minoh Na; Yangho Kim (Elsevier, 2024)
Objectives: The present paper aimed to examine whether an aging workforce is associated with an increase in work-related fatal injuries and to explore the underlying reasons for this potential increase. Material and methods: Aged workers were defined as those who were at least 55 years old. Work-related fatalities were assessed in aged and young workers who were registered with the workers' compensation system in 2021 in the Republic of Korea. Total waged workers, based on raw data from the Local Area Labor Force Survey in 2021, were used as the denominator to estimate the work-related fatality rates. Results: Most work-related fatalities in the aged workers occurred among individuals working in the "construction sector" (58.9%), those with "elementary occupations (unskilled workers)" (46.1%), and those with the employment status of "daily worker" (60.8%). The estimated incidence (0.973/10,000) of work-related fatalities among aged workers was about four times higher than that (0.239/10,000) among younger workers. "Falling," "collision," "struck by an object," and "trip and slip" were more frequent types of work-related fatalities among aged workers relative to young workers. The category of "buildings, structures, and surfaces" was a more frequent cause of work-related fatalities among aged workers than among young workers. Conclusions: Aged workers had a higher incidence of work-related fatalities than young workers. Frequent engagement in precarious employment and jobs, coupled with the greater physical vulnerability of aged workers, were likely causes of their higher level of work-related fatal injuries.